Potensi Ekstrak Kelopak Bunga Rosela (Hibiscus sabdariffa L.) dalam Menghambat Denaturasi Protein secara In Vitro - Vikasari, Suci Nar; Septiani, Vina; Rahajeng, Dea Julianti (Pengurus Pusat Ikatan Apoteker Indonesia, 2024)
Inflammation is a normal response to injury, which is characterized by protein and fluid leakage from blood vessels, causing pain and swelling. This study was conducted to determine the in vitro protein denaturation inhibition activity of roselle calyx extract (Hibiscus sabdariffa L.). Roselle flowers were extracted in stages by maceration with n-hexane, ethyl acetate, and 96% ethanol. The comparator used was diclofenac sodium. Several concentration series of extracts and comparators were prepared, and protein denaturation inhibition experiments on bovine serum albumin (BSA) were conducted. The parameters measured were the inhibition value of protein denaturation at each concentration and the value of 50% inhibition (IC50). The results of the study indicated that n-hexane extract, roselle calyx ethyl acetate, and roselle calyx ethanol (96%) could inhibit protein denaturation. Roselle calyx n-hexane extract exhibited an IC50 46.6748g/mL, ethyl acetate extract exhibited an IC50 225.8391g/mL, and 96% ethanol extract exhibited an IC50 191.5105g/mL, whereas diclofenac sodium exhibited an IC50 8.5437g/mL. The conclusion revealed that roselle calyx extracts in n-hexane, ethyl acetate, and 96% ethanol display potentials as anti-inflammatory potential agents by inhibiting protein denaturation.